Local Heat Transfer and Pressure Drop in a Rotating Two-Pass Ribbed Rectangular Channel - Shou-Shing Hsieh; Hsiu-Cheng Liao (International Journal of Rotating Machinery)
The influences of rotation and uneven heating condition as well as passage aspect ratio on the local heat transfer coefficient and pressure drop in a rotating, two pass ribroughened (rib height e/DH≈0.27; rib pitch p/e=8) rectangular channel with a crosssection aspect ratio of 3 was studied for Reynolds numbers from 5000 to 25,000 and rotation numbers from 0 to 0.24. Regionally averaged Nusselt number variations along the duct have been determined over the trailing and leading surfaces for two pass straight channels and U-bend region. Implementing with the data from Hsieh and Liu (1996) for AR=1 and 1.5 with p/e=5 and e/DH=0.17 and 0.20, passage aspect ratio effect was further examined. Furthermore, data for 180∘ U-bend region with ribroughened turbulator on heat transfer were also measured. It was found that a complicated three-dimensional accelerated flow and secondary flow in this U-bend region caused higher heat transfer on both leading/trailing walls. Enhancement performance ratios are also presented and discussed. Results again indicate a slight decrease in heat transfer coefficient for an increase in passage aspect ratio as compared to those of previous studies.